Draft Genome Sequence and Transcriptome Analysis of the Wine Spoilage Yeast Dekkera Bruxellensis lamap2480 Provides Insights into Genetic Diversity, Metabolism and Survival - Martinez-Fernandez, C; Ganga-Munoz, M; Godoy-Olivares, L; Cubillos-Riffo, F (Blackwell Publishing Ltd, 2014)
Dekkera bruxellensis is the major contaminant yeast in the wine industry worldwide. Here, we present the draft genome sequence of D. bruxellensis LAMAP2480 isolated from a Chilean wine. Genomic evidence reveals shared and exclusive genes potentially involved in colonization and survival during alcoholic fermentation. Genomic evidence reveals shared and exclusive genes potentially involved in colonization and survival during alcoholic fermentation. © 2014 Federation of European Microbiological Societies.